Architectural design - Anderson, Jane, 1973- 4 0 16; 5 (London : Bloomsbury Visual Arts, 2019)
Follows each step in the process of architectural design from the studio to construction and occupation of a structure.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Architectural design. -- 20; 20; 2